2018
DOI: 10.1021/acs.est.8b02431
|View full text |Cite
|
Sign up to set email alerts
|

Can Sanitation Technology Play a Role in User Perceptions of Resource Recovery? An Evaluation of Composting Latrine Use in Developing World Communities in Panama

Abstract: There remains a large unmet need for sanitation access throughout the world that compromises both human and environmental health. Opportunities exist to employ sanitation systems that better utilize and recover scarce resources from excreta such as water, energy, and nutrients. However, technologies such as a composting latrine may require more maintenance and close handling of feces compared to other sanitation technologies. This study aims to evaluate how use of on-site composting latrine technology and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…Current social challenges (e.g. users' perception of excreta for resource recovery (Naughton et al, 2018)) and technical challenges (e.g. scaling up operations without increasing contamination risks) exist to its widespread implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Current social challenges (e.g. users' perception of excreta for resource recovery (Naughton et al, 2018)) and technical challenges (e.g. scaling up operations without increasing contamination risks) exist to its widespread implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Composting toilets may also be associated with lower satisfaction, though this relationship is less definitive ( p = 0.094). Composting toilets are a type of ecological sanitation system designed to provide onsite treatment, and they may be common where soil conditions, shallow groundwater tables, and flooding hinder pit latrine construction and excreta containment. Past installations of composting toilets in Bwaise were likely (partially) motivated by groundwater and flooding conditions, but there is now a perception among local officials and residents that such conditions increase moisture within composting chambers and impair treatment performance (perhaps due to imperfect sealing during construction, allowing water to enter) . Notably, these perceived issues informed our scenario modeling (discussed below).…”
Section: Resultsmentioning
confidence: 99%
“…Container-based toilets typically employ a urine-diverting design, potentially suggesting similarities with composting latrines (which, as surveys showed, may be viewed negatively). Urine-diverting facilities can also place greater operation and maintenance responsibilities on users, face clogging issues in urine pipes, and generate odors if mismanaged, potentially reducing user satisfaction. ,, Moreover, container collection can entail risks for sanitation workers, while containers that go uncollected would accumulate and create health hazards, jeopardizing sustained system functionality. However, well-organized collection schemes may increase satisfaction by ensuring smooth operation and potentially employing local residents (workers familiar with settlement geography will likely improve transport efficiency).…”
Section: Resultsmentioning
confidence: 99%
“…There are also extensive resources available at the Sustainable Sanitation Alliance Library (https://www.susana.org/en/knowledge-hub/resources-and-p ublications/library). A recent journal article evaluated how use of technologies discussed in this chapter and other demographic characteristics influences users' perceptions of excreta for optimum resource recovery (Naughton et al, 2018).…”
Section: Figure 1 Location Of Composting and Dry Desiccating Toiletsmentioning
confidence: 99%
“…pathogen inactivation, urine and anal cleansing water may be diverted from the toilet for collection or conveyance to the subsurface (Naughton et al (2018) have reported that clogging of urine diversion tubing is a commonly reported issue so care needs to be made in maintenance and proper sizing of the tubing) toilet design and operation can be integrated with 3.…”
Section: Figure 1 Location Of Composting and Dry Desiccating Toiletsmentioning
confidence: 99%